Acceptance of illness and quality of life of patients under long-term home nursing care - Bożena Majchrowicz; Krystyna Kowalczuk; Katarzyna Tomaszewska (Frontiers in Public Health)
IntroductionLong-term home nursing care is care for patients who do not qualify for inpatient treatment, and for various reasons are unable or unwilling to receive care in long-term facilities. Patients receiving such care are of various ages, with varying degrees of disabilities that limit their independent functioning. Their condition is caused by chronic diseases, traffic accidents or genetic diseases. In many cases, in a short period of time they turn from being professionally, socially active people to becoming dependent on third parties. Acceptance of one’s own illness can reduce the negative feelings associated with it, allows one to maintain self-esteem and is of great importance for the subjective feeling of life satisfaction.AimThe aim of this study was to demonstrate whether a relationship exists among respondents receiving long-term home nursing care between the level of functional capacity, acceptance of illness and subjective assessment of life satisfaction.Materials and methodsThe authors conducted a study among 240 patients under long-term home nursing care in Subcarpathian Voivodeship in Poland. The study used a diagnostic survey as a survey technique. The research tool was a survey questionnaire containing questions on sociodemographic data and standardized research tools: Barthel Scale, Acceptance of Illness Scale (AIS) and Satisfaction with Life Scale (SWLS). Mann–Whitney U test and Spearman’s rho coefficient were used in the statistical analysis. Statistical significance of p ≤ 0.05 was assumed.ResultsThe average illness acceptance score determined by respondents according to the AIS scale was 16.11 ± 6.57. The minimum level of illness acceptance in the study group was 8 pts., while the maximum was 40 pts. In the course of the analyses, it turned out that only in the group of patients over 65 years of age, life satisfaction increased as the level of illness acceptance increased. The correlation coefficient was statistically significant (p < 0.001) and showed a clear strength of association (Spearman’s rho = 0.450). In addition, with greater functional capacity, greater life satisfaction can be observed, but in this case, although the correlation was statistically significant (p < 0.05) it is characterized by a weak strength of the relationship (Spearman’s rho = 0.178).ConclusionThe age of respondents has an impact on life satisfaction of the respondents under long-term home care. The younger the patients, the lower the acceptance of the illness and the worse the evaluation of subjective quality of life. The respondents’ level of independence and the duration of long-term care coverage have a positive effect on the acceptance of the illness and the respondents’ subjective assessment of life satisfaction.